Comparison of 6 % hydroxyethyl starch and 5 % albumin for volume replacement therapy in patients undergoing cystectomy (CHART): study protocol for a randomized controlled trial. Issue 1 (December 2015) - Kammerer, Tobias; Klug, Florian; Schwarz, Michaela; Hilferink, Sebastian; Zwissler, Bernhard; von Dossow, Vera; Karl, Alexander; Müller, Hans-Helge; Rehm, Markus
Abstract Background The use of artificial colloids is currently controversial, especially in Central Europe Several studies demonstrated a worse outcome in intensive care unit patients with the use of hydroxyethyl starch. This recently even led to a drug warning about use of hydroxyethyl starch products in patients admitted to the intensive care unit. The data on hydroxyethyl starch in non–critically ill patients are insufficient to support perioperative use. Methods/Design We are conducting a single-center, open-label, randomized, comparative trial with two parallel patient groups to compare human albumin 5 % (test drug) with hydroxyethyl starch 6 % 130/0.4 (comparator). The primary endpoint is cystatin C ratio, calculated as the ratio of the cystatin value at day 90 after surgery relative to the preoperative value. Secondary objectives are inter alia the evaluation of the influence of human albumin and hydroxyethyl starch on further laboratory chemical and clinical parameters, glycocalyx shedding, intensive care unit and hospital stay and acute kidney injury as defined by RIFLE criteria (risk of renal dysfunction, injury to the kidney, failure of kidney function, loss of kidney function, and end-stage kidney disease) criteria. Discussion There is a general lack of evidence on the relative safety and effects of hydroxyethyl starch compared with human albumin for volume replacement in a perioperative setting. Previously conducted studies of surgical patients in which researchers have compared different hydroxyethyl starch products included too few patients to properly evaluate clinical important outcomes such as renal function. In the present study in a high-risk patient population undergoing a major surgical intervention, we will determine if perioperative fluid replacement with human albumin 5 % will have a long-term advantage over a third-generation hydroxyethyl starch 130/0.4 on the progression of renal dysfunction until 90 days after surgery. Trial registration EudraCT number2010-018343-34 . Registered on 11 January 2010.